Bataille: Image and Victim. (July 2021) - Lechte, John
This article aims to reveal aspects of the relation between the image and the victim in Georges Bataille's writing, certainly as this applies to writings on art, but more particularly as it applies to Bataille's relation to the victim of torture in the photographs of Chinese lingchi punishment, which entails physical dismemberment. It will be shown that Bataille does not have a 'media specific' approach to the image but reflects Sartre's notion of the image. Critiques of Bataille's relation to the lingchi photos will be addressed (notably that of Hollywood), so as to clarify what is at stake in the relation between image and victim.